A Prospective Observational Study on the Association of the Renal Disease with the use of Proton Pump Inhibitors in a Tertiary Care Hospital - Sowjanya, Gulipalli; Amulya, Katta; Priyanka, Rama; Gayathri, Karnati; Rajesh, B.; Ramesh, Ganpisetti; Srinivasababu, P. (Indian Journal of Pharmacy Practice)
Aim: To find out the association of the renal disease with the use of proton pump inhibitors. Objective: To quantify if an association between the renal disease with the use of PPIs. Method: This is a prospective observational based study conducted in 266 patients from the gastroenterology department. The patients were selected based on inclusion and exclusion criteria. Patients who are diagnosed with acid related disease such as Gastro Esophageal Reflux Disease (GERD), Peptic ulcers including gastric ulcers, duodenal ulcers and other acid related disease, Patients with Age between 45-65 years of both genders, Patients who are willing to participate in the study, Patient with Once Daily (OD) and twice daily (BID) prescribed PPIs, Patients who are not receiving on treatment of PPIs and Patients with the chronic use (Duration of PPI treatment before presentation between 2 weeks and 6 months) of PPIs are included in the study. Patients with co-morbidities were at greater risk of kidney disease, Patients with any kidney infections, Patients prescribed with any nephrotoxic drugs, pregnant women and Paediatric population are excluded from the study. In this study we assessed for both patients who were taking PPIs and who were not taking PPIs. These patients was, follow up for three months at an interval of 15 days review was carried out. Based on these laboratory parameters like serum creatinine, Blood Urea Nitrogen (BUN), Glomerular Filtration Rate (GFR), serum electrolytes levels whether PPIs are associated in developing renal diseases can be determined. For the purpose of this analysis we compared renal function test at baseline and after a follow up for 3 months. Results: Users of PPIs compared with nonusers of PPIs, had an increased risk for double levels of creatinine, Blood Urea Nitrogen (BUN) and a decrease in Glomerular Filtration Rate (GFR). Both PPIs users and non-users were examined using chi-square test. All analyses are performed by using graph pad prism (version 7) and the results were considered statistically significant when p values were <0.05, Odds ratio OR= 7.452 (95% CI= 1.238 to 84.71) and Relative risk = 7 (95% CI= 1.155 to 43.25) this shows PPIs are associated in causing renal disease. Conclusion: Use of proton pump inhibitors is associated with increased risk of development of renal disease. Hence, it is necessary that the awareness of physicians and pharmacist is increased to the recognition of the patient complaints and the clinical manifestations.
Keywords: Proton pump inhibitors; Renal disease; Glomerular filteration rate; Blood urea nitrogen.